Customer journey in marketing (Henry Stewart Talks, 2025)
Customer journey stages & touchpoints, Journey mapping & personas, Marketing & sales integration, Multi-channel collaboration & experience, Data-driven continuous optimization, Metrics & cross-department collaboration